The value of systematic study and biobanking of explanted hearts: Insights from an international ISHLT pathology survey - Marny Fedrigo, MD PhD; Diego Perazzolo, Ing; Gerald J. Berry, MD; Annalisa Angelini, MD (JHLT Open)
This study evaluates global practices for managing explanted hearts, with a focus on tissue collection and biobanking protocols. A survey conducted through the International Society for Heart and Lung Transplantation (ISHLT) assessed responses from centers across Europe, North America, and Other Countries. Results demonstrated significant variability in tissue sampling, grossing protocols, and storage practices. While 78.8% of centers had grossing protocols, fewer (73.1%) adapted sampling based on pathology. Fresh tissue collection was prevalent in 63.5% of centers, but volumes varied: North America led with higher sampling rates (10-25 samples per heart), while Europe and Other Countries collected fewer samples. Coronary artery sampling also showed regional differences. Fresh tissues enable advanced molecular studies, while fixed tissues remain fundamental for histopathology. Standardized global protocols for sampling, storage, and reporting could enhance the clinical and research value of explanted hearts, optimizing post-transplant care and driving innovation in cardiac medicine.